A Unit Proofing Framework for Code-level Verification: A Research Agenda - Amusuo, Paschal C.; Patil, Parth V.; Cochell, Owen; Le Lievre, Taylor; Davis, James C. (IEEE/ACM International Conference on Software Engineering: New Ideas and Emerging Technologies Results (Online), 2025)
Formal verification provides mathematical guarantees that a software is correct. Design-level verification tools ensure software specifications are correct, but they do not expose defects in actual implementations. For this purpose, engineers use code-level tools. However, such tools struggle to scale to large software. The process of "Unit Proofing" mitigates this by decomposing the software and verifying each unit independently. We examined AWS's use of unit proofing and observed that current approaches are manual and prone to faults that mask severe defects. We propose a research agenda for a unit proofing framework, both methods and tools, to support software engineers in applying unit proofing effectively and efficiently. This will enable engineers to discover code-level defects early.